Management of Endometrial Hyperplasia - An Ayurveda Approach - Sachin Khairnar; Shreekant B G; Sujatha S Patil; Shreyas Swamidasan; Laxmi D R; Govind Singh (AYUSHDHARA, 2025)
Endometrial hyperplasia is the endometrial thickening with proliferation of desultorily sized and structured endometrial glands and an increased endometrial gland and stromal rate. Unopposed long- term estrogen, particularly around premenopausal or menopausal time leads to endometrial hyperplasia. In premenopausal women, pre-menopausal anovulatory cycle’s leads to unopposed estrogen action on endometrium. Endometrial hyperplasia occurs due to the patient estrogen support to the endometrial towel that leads to disordered proliferative pattern in endometrium. In uncelebrated cases it may lead to endometrial melanoma. So, early discovery and operation is necessary in this condition. In Ayurveda this condition is understood under various terms such as Vataja Yonivyapada, Lohitakshara Yonivyapada, Raktapradara, Asrigdara etc. on the basis of symptoms. The condition in Ayurveda is managed with Shodhana, shamana and Sthanika chikitsa. In the current study, a female patient aged 50yrs with the history of irregular cycles associated with extreme tiredness and severe abdominal cramps with the interval of 60 to 90 days since the past four years was treated with Ayurveda treatment for 6 weeks and significant results was observed. This study may give a new hope for the researchers to conduct randomised clinical trials with higher sample size. No adverse effects were observed throughout the study.